2019
DOI: 10.3390/ijerph16234656
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Overweight and Obesity Among Children and Adolescents in China from 1991 to 2015: A Meta-Analysis

Abstract: This meta-analysis of overweight and obesity (ow/ob) among children and adolescents in China from 1991 to 2015 provides a reference for promoting the healthy development of children and adolescents. The studies were retrieved from the China National Knowledge Infrastructure, Wanfang, and PubMed databases for the period from January 1991 to January 2018. The data were combined and analyzed, and the combined effect magnitude odds ratio and the 95% confidence interval were calculated. Publication bias was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 36 publications
1
63
0
1
Order By: Relevance
“…Existing evidence suggests that physical fitness in childhood and adolescence is associated with total and abdominal adiposity, cardiovascular disease risk factors, skeletal health, psychological symptoms, and even academic performance [ 9 ]. In recent decades, a decline in physical fitness [ 10 , 11 ] and increased prevalence of overweight and obesity [ 12 , 13 ] are well documented in both China and Japan. According to a joint survey conducted by the two countries in 2016, the prevalence of overweight and obesity was 17.5% and 5.8% higher in China than in Japan among boys and girls [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence suggests that physical fitness in childhood and adolescence is associated with total and abdominal adiposity, cardiovascular disease risk factors, skeletal health, psychological symptoms, and even academic performance [ 9 ]. In recent decades, a decline in physical fitness [ 10 , 11 ] and increased prevalence of overweight and obesity [ 12 , 13 ] are well documented in both China and Japan. According to a joint survey conducted by the two countries in 2016, the prevalence of overweight and obesity was 17.5% and 5.8% higher in China than in Japan among boys and girls [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, these results may contribute to understanding trends in obesity and metabolic health in China and inform the design of more effective individual and policy level interventions. As mentioned above, self-reported levels of physical activity are decreasing or unchanged in recent years and prevalence of obesity is increasing [ 20 , 60 ]. Knowledge of specific factors that are driving the decline in PA in youth is incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of overweight or obesity in children aged 5–19 years ranged from 6.8~58.3%, and more than 381 million children had overweight/obesity in 2016 worldwide [ 2 ]. The prevalence rates of overweight and obesity were 11.7% and 6.8%, respectively, in 2011–2015 among children and adolescents in China [ 3 ]; the prevalence continues to increase, particularly in urban areas, and is accompanied by an increase in family income and changes in modern lifestyles [ 3 ]. A long-term cohort study found that obesity is the risk factor most strongly associated with a large carotid intima media thickness (cIMT) and an increased pulse wave velocity (PWV) in young adulthood [ 4 , 5 ], and a large cIMT is an index of an increased risk of cardiovascular disease (CVD) in adulthood.…”
Section: Introductionmentioning
confidence: 99%